2010
DOI: 10.1159/000282494
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Sex Determination and Contemporary Climate Change

Abstract: Whether species that have persisted throughout historic climatic upheavals will survive contemporary climate change will depend on their ecological and physiological traits, their evolutionary potential, and potentially upon the resources that humans commit to prevent their extinction. For those species where temperatures influence sex determination, rapid global warming poses a unique risk of skewed sex ratios and demographic collapse. Here we review the specific mechanisms by which reptiles with temperature-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
182
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(200 citation statements)
references
References 167 publications
1
182
0
Order By: Relevance
“…For these reasons, clutch phenology has a potentially significant effect on nest survival and success, incubation time, the ability to produce multiple clutches (Wallis et al 1999), and even hatchling sex ratio (Lewis-Winokur & Winokur 1995, Baxter et al 2008 in species with environmental sex determination (Ewert & Nelson 1991, Mitchell & Janzen 2010. In addition, clutch phenology in organisms with environmental sex determination can affect maternal and hatchling fitness via its proximate role in determining exposure to post-oviposition environmental (incubation) temperatures that differentially affect the fitness of male and female offspring (Shine 1999).…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, clutch phenology has a potentially significant effect on nest survival and success, incubation time, the ability to produce multiple clutches (Wallis et al 1999), and even hatchling sex ratio (Lewis-Winokur & Winokur 1995, Baxter et al 2008 in species with environmental sex determination (Ewert & Nelson 1991, Mitchell & Janzen 2010. In addition, clutch phenology in organisms with environmental sex determination can affect maternal and hatchling fitness via its proximate role in determining exposure to post-oviposition environmental (incubation) temperatures that differentially affect the fitness of male and female offspring (Shine 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies of C. picta have also concluded that gravid females may not have the opportunity to alter clutch sex ratios (Refsnider & Janzen 2012) or may not adjust their nesting behavior sufficiently to alter sex ratios substantially (Schwarzkopf & Brooks 1987, Schwanz & Janzen 2008, Mitchell & Janzen 2010, Renfsnider et al 2013. This supports the conclusion that weather may dominate the sex ratios of hatchling cohorts.…”
Section: Location and Structure Effectsmentioning
confidence: 99%
“…Moreover, global climate changes are already influencing wild populations of reptiles with TSD by increasing the proportion of females among recent offspring (e.g. Hays et al 2010, Mitchell & Janzen 2010, Patino-Martinez et al 2012, and G. agassizii may experience ambient temperature increases of 1−3°C in the next 100 yr (Barrows 2011, Barrows et al in press). Head-starting may offer ways to counter a climate-change-induced tendency toward excess recruitment of female chelonians in wild populations.…”
Section: Introductionmentioning
confidence: 99%
“…A problem could arise if future climate warming led to the production of a higher proportion of female hatchlings than at present or if the production of male hatchlings ceased from some beaches (Hawkes et al 2007, Fuentes et al 2009, Mitchell & Janzen 2010, Val verde et al 2010, Witt et al 2010b. Understanding sex ratios is essential for the development of population models (Owens 1997, Hamann et al 2010 for predicting effects of anthropogenic climate change (Hawkes et al 2009).…”
Section: Climate Changementioning
confidence: 99%
“…Experimental work has yet to be carried out to demonstrate if this is likely to be the case for marine turtles, although with long periods to maturity and slow growth rates, this is a challenge. In addition, early modelling work has suggested that, through climate change, the proportion of female turtles at large in the pop ulation should increase still further (Hawkes et al 2007, Fuentes et al 2009, Mitchell & Janzen 2010, Valverde et al 2010, and thus the pace of change may proceed more quickly than our un derstanding of the system before perturbation. We advocate that all marine turtle research programmes working with foraging aggregations of marine turtles routinely collect blood and tissue samples to enable secondary sex ratio estimates and assignment of source rookeries.…”
Section: Adaptation To Climate Changementioning
confidence: 99%